Cellular attachment behavior on biodegradable polymer surface immobilizing endothelial cell-specific peptide. Issue 11 (23rd July 2020) - Ohya, Yuichi; Nishimura, Kazuki; Sumida, Hiromichi; Yoshizaki, Yuta; Kuzuya, Akinori; Mahara, Atsushi; Yamaoka, Tetsuji
Abstract: Small-caliber artificial blood vessels with inner diameters of smaller than 4 mm have not been put into practical use because of early thrombus formation and graft occlusion. To realize small-caliber artificial blood vessels with anti-thrombus property and long-term patency, one of the promising approaches is endothelialization of the lumen by tissue engineering approaches. Integrin α4β1 on the endothelial cell membrane is known to act as a receptor for Arg-Glu-Asp-Val (REDV) tetra-peptide, and this peptide can be used as a specific ligand to introduce endothelial cell attachment onto the surfaces of polymer scaffold. In this study, biodegradable polymer surface immobilizing REDV peptide were prepared, and the specific attachment of endothelial cells on it was investigated as a preliminary study for tissue-engineered small-caliber blood vessels in a future application. We synthesized copolymer of ε-caprolactone and depsipeptide having reactive carboxylic acid side-chain groups (PGDCL), and REDV peptide was attached to the copolymer to give PGDCL-REDV. The attachment of human umbilical vein endothelial cells (HUVECs) were investigated for the blend polymer film prepared by mixing PGDCL and PGDCL-REDV. The obtained blend polymer films exhibited sequence- and cell-specific HUVECs attachment through REDV peptide recognition. This technique should be useful not only to obtain artificial blood vessels which induce endothelialization and but also to provide biodegradable scaffolds with specific ligands immobilized surfaces for tissue regeneration.